Modifying reaction time tasks parameters in the automated IntelliCage identifies heightened impulsivity and impaired attention in the 3xTg-AD model of Alzheimer’s disease - Judd, Jessica M.; Winslow, Wendy; McDonough, Ian; Mistry, Faizan; Velazquez, Ramon (Frontiers in Aging Neuroscience, 2024)
BackgroundThe 3xTg-AD transgenic mouse model of Alzheimer’s disease (AD) is an important tool to investigate the relationship between development of pathological amyloid-β (Aβ) and tau, neuroinflammation, and cognitive impairments. Traditional behavioral tasks assessing aspects of learning and memory, such as mazes requiring spatial navigation, unfortunately suffer from several shortcomings, including the stress of human handling and not probing species-typical behavior. The automated IntelliCage system was developed to circumvent such issues by testing mice in a social environment while measuring multiple aspects of cognition. Water consumption can serve as a primary motivator for task engagement. Once animals adapt to the cage and can access water, mice can be subjected to operant tasks. Each of the four corners of a cage contains doors to manipulate access to water, visual LED cues, and a valve allowing administration of an air puff. Previously, we detected significant impairments in 3xTg-AD mice in the IntelliCage, however a high failure rate and genotypical differences in water motivation were observed.MethodsHere, we implemented an IntelliCage paradigm where mice underwent progressively more difficult reaction time tasks to assess attention and impulsivity, behaviors mediated by the prefrontal cortex. Mice were placed in the IntelliCage at 11.5 months of age, which corresponds with the presence of widespread pathology.ResultsAs the difficulty of the reaction time tasks increased, 3xTg-AD mice exhibited lower percent Correct Responses than NonTg. When implementing varying pre-cue durations, where animals are required to wait between the initiation of the trial and the LED turning on (which then requires a nose-poke to access water), 3xTg-AD mice prematurely nose-poked on trials requiring a longer delay before a second nose poke would allow water access, demonstrating heightened impulsivity. The presence of soluble and insoluble fractions of cortical Aβ40 and 42, and phosphorylated tau epitopes threonine 181 and serine 396 confirmed the presence of neuropathological hallmarks in 3xTg-AD mice.ConclusionTogether, this study describes a novel protocol that overcomes motivational differences and detects attention and impulsivity deficits in 3xTg-AD mice utilizing the IntelliCage.